Comparative study of antioxidant activity of stem and leaves of Entada spiralis and their antibacterial properties against Erwinia chrysanthemi / Nur Khairunnisa Maha Yudden … [et al.] - Maha Yudden, Nur Khairunnisa; Nordin, Nor Nadiana; Harun, Aiza; Rosli, Nor Habibah; Abdul Aziz, Noorshilawati; Daud, Shaari (Universiti Teknologi MARA, 2019)
The present study was designed to compare the antibacterial effect between stem and leaves of Entada spiralis against soft rot bacteria Erwinia chrysanthemi and its antioxidant properties which could benefit to indigenous people. E. spiralis which locally knows as ‘sintok’ is a liana and it grows wildly in Malaysia. Indigenous people are utilizing this plant as natural washing agent and shampoo as well as ethnomedicine to cure diseases since they have little access to modern medicines. E. chrysanthemi is bacteria which commonly cause soft-rot disease of vegetables. The antibacterial activity of stem and leaves of E. spiralis against E. chrysanthemi were evaluated from disc diffusion method. The DPPH radical scavenging method and dot blot assay were utilized to see the potential of stem and leaves of E. spiralis as an antioxidant agent. The results indicated that the leaves part was more antioxidative than stem of E. spiralis with IC50 of 10.5 μg/mL. Ethyl acetate extract from stem part at concentration of 200 mg/mL was found to be the most active extract against E. chrysanthemi with the highest inhibition zone of 16.3mm. The investigation is hoped to provide basic information for the development of potent natural pesticides and natural remedy which is safer and eco-friendly.